KONSEP EKONOMI KERTHI BALI DALAM PARIWISATA BERKELANJUTAN DI DESA ADAT SERANGAN - I Made Risma M Arsha; Gede Agus Dian Maha Yoga; I Made Suasti Puja (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
Sustainable tourism is an integrated and organized effort to develop the quality of life by managing the provision, development, utilization and maintenance of resources in a sustainable manner. Attack Traditional Village is one of the tourist destinations in Denpasar City which is currently developing rapidly. Attack Traditional Village has very strong potential in the tourism sector because this village is supported by natural charm and socio-cultural values ​​as a tourist destination that is progressing along with the progress of the surrounding tourism destinations. This research will examine the Balinese Kerthi Economic concept, namely a new paradigm in economics that integrates and balances the order of life in order to create physical/material (scale) and non-physical/spiritual (niskala) prosperity and happiness in realizing sustainable tourism in the Serangan traditional village.